The Role of the International Pisa Program in Forming Students' Creative Thinking Ability in the Science of Biology (Eurasian Scientific Herald, 2023)
This article provides a general understanding of PISA, the role of the PISA program in students' lives, a creative approach to topics, and information about visual educational materials. Factors affecting students' creative thinking, importance of International PISA program in formation of students' creative thinking skills were analyzed.